Penerapan Sumber Daya Manusia yang Kompetititf terhadap Produktivitas Karyawan pada Rumah Makan Angkringan Lestari Maumere - Maria Modesta Missi Mone; Kristina Asmiyati; Katarina Kaur; Maria Teresa Kowalska; Maria Sefriani Trisnayati (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2026)
This study aims to determine the application of competitive Human Resource Management (HRM) to employee productivity at Angkringan Lestari Restaurant. Human resources are a crucial factor in the success of a business, particularly in the culinary industry, which relies heavily on service quality, work speed, discipline, and employee ability to serve customers. Competitive HRM implementation is achieved through improving employee performance, knowledge, skills, motivation, discipline, and assigning appropriate responsibilities to employees to optimally increase work productivity.The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The study was conducted at Angkringan Lestari Restaurant, focusing on the application of HRM to support employee productivity. The results indicate that the implementation of competitive HRM positively impacts employee productivity. This is evident in improved service quality, punctuality, employee collaboration, and increased customer satisfaction with the service provided.Furthermore, work performance, knowledge, and skills are important factors in increasing employee productivity. However, several obstacles remain, such as limited job training and a lack of continuous competency development. Therefore, efforts are needed to improve the quality of human resources through training, work motivation, and skills development so that employee productivity can continue to increase and be able to compete competitively.